2022
DOI: 10.1002/wjo2.5
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and gustatory dysfunctions of COVID‐19 patients in China: A multicenter study

Abstract: Introduction: With the spread of the epidemic worldwide, an increasing number of doctors abroad have observed the following atypical symptoms of coronavirus disease 2019 (COVID-19): olfactory or taste disorders. Therefore, clarifying the incidence and clinical characteristics of olfactory and taste disorders in Chinese COVID-19 patients is of great significance and urgency.Materials and Methods: A retrospective study was conducted, which included 229 severe acute respiratory syndrome coronavirus 2 confirmed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Since we conducted our study on hospitalized patients with mild-to-moderate COVID-19, we could not have the opportunity to examine the effect of smell dysfunction on prognosis. Another study reported that loss of smell were associated with better prognosis ( 23 ). Although, basing on the current knowledge, there is a general belief that olfactory dysfunction is a positive prognostic factor, new studies are needed on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Since we conducted our study on hospitalized patients with mild-to-moderate COVID-19, we could not have the opportunity to examine the effect of smell dysfunction on prognosis. Another study reported that loss of smell were associated with better prognosis ( 23 ). Although, basing on the current knowledge, there is a general belief that olfactory dysfunction is a positive prognostic factor, new studies are needed on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Mendonça et al reported a significantly higher prevalence of OD amongst patients with more severe COVID-19 disease. Li et al [ 100 ] reported that only a small proportion of patients with OD developed severe and critical illness was relatively small. Yan et al [ 101 ] also found that patients who required admission for COVID-19 were significantly less likely to report OD.…”
Section: Sinonasal Sars-cov-2 Infectionmentioning
confidence: 99%
“…Consequently, the oral cavity emerges as a gateway for viral transmission and disease progression, necessitating a comprehensive understanding of its involvement in the context of COVID-19. Indeed, emerging evidence from multiple studies corroborates the occurrence of oral lesions and related alterations, such as gustatory disorders, olfactory dysfunction, and xerostomia, in individuals afflicted with COVID-19 [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%